NOVEL CONTROL APPROACH FOR OPTIMAL POWER FLOW IN HYBRID WIND-PHOTOVOLTAIC-DIESEL GENERATION SYSTEMS - Diep, Thang; Quang, Nguyen Phung; Huy, Nguyen Duc (Journal of Computer Science and Cybernetics, 2017)
The paper deals with a formulation of an analytical control model for optimal power flow in an islanded microgrid (MG). In an MG with load change, wind power fluctuation, sun irradiation power disturbance, that can significant influence the power flow, and hence the power flow control problem in real life system faces some new challenges. In order to maintain the balance of power flow, a diesel engine generator (DEG) needs to be scheduled. The objective of the control problem is to find the DEG output power by minimizing the total cost of energy. Using the Bellman principle, the optimality conditions obtained satisfy the Hamilton-Jacobi-Bellman equation, which depends on time and system states, and ultimately, leads to a feedback control or to the so called energy management to be implemented in a SCADA system